Rumah Peduli Gizi untuk Pencegahan dan Pemulihan Gizi Berbasis Komunitas - Susyanto1, Bambang Edi; Huriah, Titih; Ramasari, Farindira Vesti; Aprilia, Suci (Universitas Muhammadiyah Yogyakarta, 2019)
Malnutrition caused by carbohydrate and / or protein deficiency still threatens Indonesian children, including nutritionalanemia due to iron deficiency, Iron deficiency anemia (IDA)which is the most prevalent anemia but neglectedby public attention. The participation of the community in the prevention and treatment of malnutrition in childrenstarts with the active participation of pregnant women in routine checks during pregnancy, supplementary feedingto children under five and monitoring the nutritional status of their children. The role of health cadres in thecommunity is very important because they are the motor of community nutrition development activities in theirarea. Community service is intended to prevent and improve malnutrition in children through improving the qualityof Posyandu (Pos Pelayanan Terpadu/Integrated Health Post) activities, monitoring of growth and health of underfive years old children and administration of supplementary feeding for infants and children. This program isdedicated for increasing knowledge and skills of cadres and mothers of infants and under five year hildren inCokrowijayan and Sukunan villages in Banyuraden Village, Gamping Sub-District, Sleman . The activities carriedout in this service were in the form of malnutrition prevention and recovery workshops for children involving healthleaders in Cokrowijayan and Sukunan Villages in Banyuraden Village and village youth leaders, including theoryand practice. Additionally, there was assistance in measuring the anthropometry for growth monitoring. Otherassistance provided was in he form of additional food for infants and under five year children. In this program, Timof FKIK UMY (Medical Faculty Team of Muhammadiyah Yogyakarta University) also carried out the assessment ofthe knowledge and practice of mothers of infants and under five year children in terms of nutrition care. Themeasurement results are reported descriptively and analytically.